Direction of Foreign Trade of Nepal - Shrestha, Rohit Kumar (Dristikon: A Multidisciplinary Journal, 2021)
It is foreign trade that deals with the transaction of goods, including services, financial flows, and the movement of factors of production, like labor, capital, and entrepreneurship. The objective of the 15th plan for Nepal is to reduce the trade deficit by increasing production, managing imports, and diversifying trade on a country-wise and a goods-wise basis for export promotion and to maintain foreign exchange stability, external sector stability, and a targeted foreign exchange reserve. The purpose of this research is to assess the direction of Nepalese foreign trade. The author has not found the updated research work of the type. This is a descriptive study that uses secondary data. The analysis relies on simple mathematical tools such as ratios and percentages. The data clearly expresses a huge trade deficit. The rapidly increasing trade imbalance indicates that foreign trade policy needs to be evaluated and improved. In 2019/20, foreign trade in Nepal was adversely affected as compared to previous study years. Nepal's major trade partner is India in terms of imports, exports, trade balance, and total trade. In 2019/20, India's share of total exports stood at 71.8 percent, which was 64.6 percent last year. In total imports, India's share remained at 61.4 percent, as compared to 64.7 percent last year. The findings help the government of Nepal, researchers, practitioners, and learners to know the existing direction of foreign trade of Nepal.